FATORES ASSOCIADOS À GRAVIDEZ NA ADOLESCÊNCIA EM CAXIAS, MARANHÃO, EM 2012/2013 - Vilanova, Maria da Conceição Costa (2014)
Teenage pregnancy is a serious social problem and public health. It is also perceived as a multifactorial and complex phenomenon. Planned or not, has different meanings according to the economic, cultural and social context in which it is inserted. This study was developed in order to study the risk factors associated with the occurrence of teenage pregnancy in Caxias - MA. A cross-sectional analytical study was conducted. Of the 374 women interviewed, 35.7% were teenagers. The variables were sociodemographic, economic, those relating to health data and lifestyle. Risk factors for teenage pregnancy, after logistic regression analysis were: not having paid work (PR: 1.44, 95% CI 1.02 to 2.05), divorced parents (PR: 1.39; 95% CI = 1.07 to 2.05) and habitual alcohol use (RP:. 1.21, 95% CI = 1.09 to 1, 35). Concluded that these factors must be taken into consideration in developing strategies to prevent teenage pregnancy under the Public Health programs.